On nonparametric estimation: With a focus on agriculture - Fare, Rolf; Grosskopf, Shawna; Pasurka, Carl; Martins-Filho, Carlos (Annual Reviews, 2013)
We review nonparametric estimation of efficiency and productivity, by which we mainly mean activity analysis, or data envelopment analysis (DEA). The review covers topics that we hope will be of special interest to those doing research in the realm of agriculture. We also include a brief appendix addressing nonparametric estimation from an econometric perspective.